Deep brain stimulation for substance use disorder: a systematic review and meta-analysis - Shaheen, Nour; Shaheen, Ahmed; Sarica, Can; Singh, Arun; Zanaty, Mario; Johari, Karim; Yang, Andrew; Zesiewicz, Theresa; Dalm, Brian; Bezchlibnyk, Yarema; Lozano, Andres M.; Flouty, Oliver (Frontiers in Psychiatry, 2023)
Objective: Substance use disorder (SUD) is a significant public health issue with a high mortality rate. Deep Brain Stimulation (DBS) has shown promising results in treating SUD in certain cases. In this study, we conducted a meta-analysis to evaluate the efficacy of DBS in the treatment of SUD and reduction of relapse rates. Methods: We performed a thorough and methodical search of the existing scientific literature, adhering to the PRISMA guidelines, to identify 16 original studies that fulfilled our inclusion criteria. We used the evidence levels recommended by the Oxford Centre for Evidence-Based Medicine to assess bias. The R version 4.2.3 software was utilized to calculate the mean effect size. We estimated study heterogeneity by employing tau2 and I2 indices and conducting Cochran's Q test. Results: The results showed that DBS treatment resulted in a significant improvement in the clinical SUD scales of patients, with an average improvement of 59.6%. The observed relapse rate was 8%. The meta-analysis estimated a mean effect size of 55.9 [40.4; 71.4]. Heterogeneity analysis showed a large degree of heterogeneity among the included studies. Subgroup and meta-regression analysis based on age and SUD type suggested that DBS may be more effective for patients above 45 years of age, and for alcohol and opioid addiction compared to nicotine addiction. Conclusions: The current literature suggests that DBS has a moderate effect on SUD symptoms. However, the limited number of studies and small sample size indicate that more research is needed to better understand the factors that influence its effectiveness.